RAB2 regulates the formation of autophagosome and autolysosome in mammalian cells. Issue 10 (3rd October 2019) - Ding, Xianming; Jiang, Xiao; Tian, Rui; Zhao, Pengwei; Li, Lin; Wang, Xinyi; Chen, She; Zhu, Yushan; Mei, Mei; Bao, Shilai; Liu, Wei; Tang, Zaiming; et al.
ABSTRACT: Multiple sources contribute membrane and protein machineries to construct functional macroautophagic/autophagic structures. However, the underlying molecular mechanisms remain elusive. Here, we show that RAB2 connects the Golgi network to autophagy pathway by delivering membrane and by sequentially engaging distinct autophagy machineries. In unstressed cells, RAB2 resides primarily in the Golgi apparatus, as evidenced by its interaction and colocalization with GOLGA2/GM130. Importantly, autophagy stimuli dissociate RAB2 from GOLGA2 to interact with ULK1 complex, which facilitates the recruitment of ULK1 complex to form phagophores. Intriguingly, RAB2 appears to modulate ULK1 kinase activity to propagate signals for autophagosome formation. Subsequently, RAB2 switches to interact with autophagosomal RUBCNL/PACER and STX17 to further specify the recruitment of HOPS complex for autolysosome formation. Together, our study reveals a multivalent pathway in bulk autophagy regulation, and provides mechanistic insights into how the Golgi apparatus contributes to the formation of different autophagic structures. Abbreviations: ACTB: actin beta; ATG9: autophagy related 9A; ATG14: autophagy related 14; ATG16L1: autophagy related 16 like 1; BCAP31: B cell receptor associated protein 31; BECN1: beclin 1; Ctrl: control; CQ: chloroquine; CTSD: cathepsin D; DMSO: dimethyl sulfoxide; EBSS: Earle's balanced salt solution; EEA1: early endosome antigen 1; GDI: guanine nucleotide dissociation inhibitor; GFP: green fluorescent protein; GOLGA2: golgin A2; HOPS: homotypic fusion and protein sorting complex; IP: immunoprecipitation; KD: knockdown; KO: knockout; LAMP1: lysosomal associated membrane protein 1; LC3: microtubule-associated protein 1 light chain 3; OE: overexpression; PtdIns3K: class III phosphatidylinositol 3-kinase; SQSTM1/p62: sequestosome 1; RAB2: RAB2A, member RAS oncogene family; RAB7: RAB7A, member RAS oncogene family; RAB11: RAB11A, member RAS oncogene family; RUBCNL/PACER: rubicon like autophagy enhancer; STX17: syntaxin 17; TBC1D14: TBC1 domain family member 14; TFRC: transferrin receptor; TGOLN2: trans-golgi network protein 2; TUBB: tubulin beta class I; ULK1: unc-51 like autophagy activating kinase 1; VPS41: VPS41, HOPS complex subunit; WB: western blot; WT: wild type; YPT1: GTP-binding protein YPT1.